Brazil’s grand border strategy: challenges of a new critical thinking in a modern era - Dhenin, Miguel; Pellegrino Correa, Paulo Gustavo (Revista Brasileira de Estudos de Defesa, 2017)
This paper aims to offer a critical perspective regarding Brazil's border policies and its military presence. For decades, the Brazilian Armed Forces emphasized the 'Security and Development' doctrine as the solution to solve the many issues of the remote areas of the Amazon. In the late 1980's, even with the end of the Military Regime, such practices continued to dominate the agenda of policymakers. Nowadays, Brazil's young democracy faces new challenges regarding its 'brown areas', as O'Donnell theorized them. Our main goal here is to stress the lack of a critical thinking in the process of transformation of the regional reality. We evaluated the situation according to recent data gathered during several field trips in the Amazon region. The absence of a government presence, often pointed out as a strategic weakness by the military authorities, neglect the presence of various actors (population, NGOs, for example) committed to security. We argue that it is essential for the military to cooperate more with civilians, instead of militarizing the borders, to guarantee a safe presence for the population, and not only the security of a territory.